The Kashmir Tinderbox: International Media Coverage of the Revocation of Article 370 - Mohydin, Ravale (The Political Economy of Communication, 2021)
International media has a pivotal role to play in the course of any conflict, and the Kashmir dispute is no different. Building on the limited number of previous Kashmir-related studies, this article illustrates the differences in conflict frames used by American (CNN) and Turkish (TRT World) news outlets in regard to media coverage concerning the revocation of Article 370 of the Indian Constitution, arguably a key turning point in the trajectory of the Kashmir dispute. I will uncover factors underpinning the clash of frames including geopolitical priorities, news outlets’ political-economic organization and the global communications environment. Setting this research against previous studies allows one to explain the distinctiveness of the coverage across channels and within the same news outlets over time, i.e., before and after the revocation of Article 370. Ultimately, the article seeks to uncover the role of international media in positioning and packaging the Kashmir dispute and explores the potential consequences of this for conflict resolution.